Towards a Computational Model of Argumentation Schemes in Agent-Oriented Programming Languages - Panisson, Alison R.; Bordini, Rafael H. (2020 IEEE/WIC/ACM International Joint Conference on Web Intelligence and Intelligent Agent Technology (WI-IAT), 2020)
There are many benefits of using argumentation-based techniques in multi-agent systems, as clearly shown in literature. Such benefits come not only from the expressiveness that such approaches bring to agent communication but also from the reasoning and decision-making capabilities under conditions of conflicting and uncertain information that argumentation brings to autonomous agents. When developing multi-agent applications in which argumentation will be used to improve agent communication and reasoning, argumentation schemes (i.e., reasoning patterns for argumentation) are useful in addressing the requirements of the application domain in regards to argumentation (e.g., defining the scope in which argumentation will be used by agents in that particular application). In this work, we propose a general argumentation framework that takes into account the particular structure of argumentation schemes at its core. This paper formally defines that framework and experimentally evaluates its implementation.